GC-MS Analysis and In Silico Docking Study of Active Antifungal Components of Entada rheedei Spreng. (Seeds) (International Journal of Pharmaceutical Sciences and Drug Research, 2023)
Entada rheedei Spreng., is a liana or a climber belonging to the family Fabaceae and is widely distributed in tropical and sub-tropical areas. The seeds of Entada rheedei Spreng. has been found to contain important phytoconstituents such as phenolics, thioamides and saponins. In this study, we investigated the antifungal properties of Entada rheedei Spreng. and imply in silico methods to study its bio-active phytoconstituents. The aqueous extract of the seeds exhibited significant antifungal inhibitions against Aspergillus flavus and Aspergillus fumigatus. GC-MS analysis reveals the presence of 13 bioactive compounds that could be potent fungal inhibitors. Subsequently, in silico Molecular docking analysis recognised benzoic acid, 2, 4-bis (trimethylsilyloxy)- trimethylsilyl ester as the active antifungal constituent of the aqueous extract with a docking score of -8.0570 and -9.4564 kcal/mol against Aspergillus flavus and Aspergillus fumigatus respectively. The insilico studies were further backed by 100 ns Molecular Dynamics simulation studies. This study can thus lead to the production of potent plant based antifungal drugs.